Counseling services and their relation to assertive behavior of female students with learning disabilities at primary schools in Madinah - A teacher’s perspective - Al-Moteiri, Hala Masaad (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the counseling services provided to students with learning difficulties in primary schools and to reveal their level of affirmative behavior from the point of view of their teachers in Madinah. The study sample consisted of (52) female teachers, and the results indicated that the degree of counseling services provided to students with learning difficulties is higher than the average. The guidance provided and the affirmative behavior of students with learning difficulties in primary schools in Madinah, and in light of these results, the researcher recommends several recommendations, the most important of which are: The development of the Ministry of Education for training programs that aspire to improve the skills of school counselors, and the adoption of approaches and policies that require cooperation between counselors, teachers and special education teachers The researcher also recommends educational counselors to provide counseling programs for behavioral development As an affirmation for students, teachers and parents.
Keywords: counseling services; assertive behavior; learning difficulties